Analisis Yuridis terhadap Penentuan Unsur Wanprestasi dan Kerugian dalam Kasus Fraud Telemedicine: Studi Perspektif Hukum Perdata pada Era Layanan Kesehatan Digital - Badjuka, Muhammad Alfitho (Journal Evidence Of Law, 2025)
This article discusses the legal analysis of the elements of breach of contract and damages in a fraud case that occurred in telemedicine services, highlighting the civil law perspective in the era of health digitalization. Telemedicine services provide efficient access to healthcare, but are vulnerable to fraudulent practices, such as false diagnoses, unreasonable billing, or manipulation of medical data. This study employs a normative legal method by examining relevant regulations, jurisprudence, and doctrines, while highlighting the complexity of proving breach of contract in electronic contracts between patients and service providers. The findings reveal that breach of contract may arise from violations of contract terms, including failure to provide medical services in accordance with standards or lack of transparency in information. Proving breach of contract and damages, both material and immaterial, poses a unique challenge amid digital data control by providers and low legal literacy among patients. Harmonization of regulations in the fields of health, consumer protection, and personal data protection is essential to strengthen legal protection for patients. This article recommends the importance of strengthening electronic evidence authentication mechanisms and synergy between legislators, regulators, and telemedicine industry players in formulating adaptive guidelines to ensure fairness, certainty, and legal protection within the digital healthcare ecosystem. Responsive civil law enforcement is considered crucial to address challenges and ensure maximum protection for all parties involved.